2021
DOI: 10.35188/unu-wider/2021/973-0
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the performance and competitiveness of Tanzania’s manufacturing exports

Abstract: This study sought to examine the main constraints to manufacturing export competitiveness in Tanzania. Using panel data for the period 1997–2018, the study established that supply-side factors dominate demand-side factors in explaining manufacturing export competitiveness. Specifically, the results revealed that foreign direct investment and tariffs have a negative and significant effect on export competitiveness in Tanzania, while infrastructure, total investment, labour productivity, and high institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Sustainable FoF-PFs with high-quality control and financial performance are essential for Tanzania's economic and agricultural transformation (Adeleye et al, 2020). FoF-PFs in Tanzania might take the country to the top of world production and boost agricultural product value, transforming the economy (Misati & Ngoka, 2021) and achieving sustainable development (Haraguchi et al, 2018;National Bureau of Statistics, 2018;Reardon et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Sustainable FoF-PFs with high-quality control and financial performance are essential for Tanzania's economic and agricultural transformation (Adeleye et al, 2020). FoF-PFs in Tanzania might take the country to the top of world production and boost agricultural product value, transforming the economy (Misati & Ngoka, 2021) and achieving sustainable development (Haraguchi et al, 2018;National Bureau of Statistics, 2018;Reardon et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Again, some of the technology and capital-intensive products (e.g., machinery) may be imported before being supplied to M&Q. This is because manufacturing in Tanzania still relies on basic technologies and skills [44]. From a forward linkages perspective, M&Q is not one of the main suppliers of inputs to 'The manufacture of electrical and machinery' (E06), including pumps, compressors, bearings, and gears, although it may indirectly contribute to electrical and machinery production through 'The manufacture of metal products' (E05) and 'The manufacture of petroleum, chemical and non-metallic mineral products' (E04), which are the first-and third-ranked sectors in the list of suppliers to 'The manufacture of electrical and machinery' (E06), including pumps, compressors, bearings, and gears.…”
Section: Manufacturing Sectorsmentioning
confidence: 99%
“…The authors found that the economic crisis significantly and negatively impacted firms' innovation indicators and efforts regarding research and development [5]. The work by Misati and Ngoka (2024) emphasizes that changes in business models, caused by global economic downturns, require food industry enterprises to review their strategies and introduce new approaches to export and competitiveness [6]. Bivona and Cruz (2021) shows how various business model innovations help small and medium enterprises in the food industry overcome turbulent and uncertain conditions, such as the economic crisis caused by COVID-19.…”
mentioning
confidence: 98%